Comparison of contrast enhancement and image quality using different contrast administration protocols for routine abdominal Computed Tomography (CT) in two centers - Sian, Poh Choon (2021)
Background: Computed tomography (CT) scanning is a diagnostic imaging procedure that uses x-rays to build images of the body. CT scanning is an extremely common imaging modality in modern medicine. Contrast enhancement is the key component in CT scanning which helps to distinguish abnormal from normal body structure. Numerous interacting factors can affect the quality of CECT images, which may be divided into three categories: patient, contrast medium and CT scanning. A lack of standardization has resulted in heterogeneous dosing regimens across radiology practices. The purpose of this study is to compare the effect of the two different scanning protocols mentioned above on the contrast enhancement and image quality of CECT abdomen. Methods: A cross-sectional study was conducted in Hospital Universiti Sains Malaysia (HUSM), Kota Bharu, Kelantan, Malaysia and Advanced Medical and Dental Institute (AMDI), Kepala Batas, Penang, Malaysia on 336 patients aged 18 and above with contrast-enhanced CT (CECT) scan of abdomen between January 2017 and December 2019. Images of the CECT abdomen using different protocol were collected retrospectively from these two centres: 168 patients from HUSM, using fixed contrast volume with fixed time-delay technique, and 168 patients from AMDI using weight-based contrast volume with automatic bolus tracking technique. Quantitative assessment was performed by measuring the degree of enhancement in region of interest and were quantified in Hounsfield unit (HU). Mean enhancement values from each protocol was assessed and compared using independent t-test. Qualitative assessment was performed in which the images will be graded by radiologist using 4